2008
DOI: 10.1254/jphs.fp0071648
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Memory Impairment Without Apoptosis Induced by the Combination of Beta-Amyloid Oligomers and Cerebral Ischemia Is Related to Decreased Acetylcholine Release in Rats

Abstract: Abstract. The purpose of the present study was to examine the effect of beta-amyloid (Aβ) oligomers, not the fibrils that make up Aβ plaques, on spatial memory and the cholinergic system in rats. Recently, several researchers have suggested that small assemblies of Aβ, Aβ oligomers, caused memory loss during the early stages of Alzheimer's disease without showing cell death. In the present study, the combination of Aβ oligomers and cerebral ischemia, but not cerebral ischemia alone, significantly impaired spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…In comparison with the report of researchers indicating the effects of CDP-choline on ischemic injury, the dose used in this report is not a low dose (9,10,23), and a previous study reported that 3 mg/kg of donepezil significantly improved the spatial memory impairment induced by the combination of β-amyloid and cerebral ischemia (30). The improvement effect of 1000 mg/kg of CDP-choline on the impaired memory by ischemia is not inferior to that that of 3 mg/kg of donepezil, which was therefore thought to be sufficient to exert the ameliorative effect on memory impairment.…”
Section: Discussionmentioning
confidence: 68%
“…In comparison with the report of researchers indicating the effects of CDP-choline on ischemic injury, the dose used in this report is not a low dose (9,10,23), and a previous study reported that 3 mg/kg of donepezil significantly improved the spatial memory impairment induced by the combination of β-amyloid and cerebral ischemia (30). The improvement effect of 1000 mg/kg of CDP-choline on the impaired memory by ischemia is not inferior to that that of 3 mg/kg of donepezil, which was therefore thought to be sufficient to exert the ameliorative effect on memory impairment.…”
Section: Discussionmentioning
confidence: 68%
“…Oligomeric Aβ was prepared as previously described. 8) Aβ40 and Aβ42 peptides were dissolved in a N-(2-hydroxyethyl) piperazine-N′-2-ethanesulfonic acid (HEPES)-buffered solution to a final concentration of 10 µM. They were mixed at a molar ratio of 10 : 1 of Aβ40 : Aβ42 and incubated at 37°C for 150 min (Oligomeric Aβ solution).…”
Section: Methodsmentioning
confidence: 99%
“…8) Briefly, rats were anesthetized with intraperitoneal injection of 50 mg/ kg of sodium pentobarbital (Tokyo Kasei, Tokyo, Japan) and immobilized in a stereotaxic apparatus. The bilateral vertebral arteries were electrocauterized using a bipolar coagulator (MICRO-3D; Mizuho Industrial Co., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations